INFORMATION SYSTEMS AND INTERNAL AUDIT IN STRENGTHENING THE FINANCIAL STATEMENTS OF THE MUHAMMADIYAH REGIONAL LEADERSHIP OF CIREBON REGENCY - Endah Nurhawaeny Kardiyati; Abdul Karim; Afip Afip (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
n this era of globalization, every institution in Indonesia has financial records that have different reputations and needs. The performance of the institution can be measured and assessed through measured and estimated financial records, whose quality is revealed based on facts and not through engineering. Otherwise, it will result in less effective decision-making for users of financial records who do not have accounting capabilities. So that in a certain period of time it will have an impact on the institution. The purpose of the following study was to analyze the effect of implementing an accounting information system (AIS) and the role of internal audit on the quality of financial records in the Muhammadiyah regional leadership of Cirebon Regency. The following research is an associative-causal type using a population of 120 employees in the Muhammadiyah regional leadership of Cirebon Regency. The sample was determined using purposive sampling technique of 100 respondents including accounting, treasurer, operator, and general staff. Primary data in the form of questionnaires from respondents were processed using multiple linear regression analysis. The results obtained show that the quality of financial records is significantly influenced by the application of AIS and the role of internal audit partially. Therefore, the implementation of AIS and the role of internal audit have a significant influence on the quality of financial records. Keywords: accounting information system, internal audit, financial records, PDM Cirebon district